Vertical ground reaction forces on rigid and vibrating surfaces for vibration serviceability assessment of structures. (1st October 2018) - Ahmadi, Ehsan; Caprani, Colin; Živanović, Stana; Heidarpour, Amin
Highlights: Introduces a unique laboratory experimental setup to investigate vertical GRFs on both rigid and flexible surfaces. 810 walking trials were performed by 18 test subjects walking at different pacing frequencies. Footbridge vibration is found to affects GRFs. GRF magnitudes reduce for harmonics in resonance with the footbridge vibration. The results can be used for more accurate vibration serviceability assessments of existing and new footbridges. Abstract: Lightweight structures are sensitive to dynamic force generated by human walking and consequently can exhibit excessive vibration responses. The imparted forces, known as ground reaction forces (GRFs), are a key input in the vibration serviceability assessment of footbridges. Most GRF measurements have been conducted on rigid surfaces such as instrumented treadmills and force plates mounted on strong floors. However, it is thought that the vibrating surface of a footbridge might affect the imparted human force. This paper introduces a unique laboratory experimental setup to investigate vertical GRFs on both rigid surface (strong floor) and a higher-frequency flexible surface (footbridge). 810 walking trials were performed by 18 test subjects walking at different pacing frequencies. For each trial, test subjects travelled a circuit of a vibrating footbridge surface followed by a rigid surface. A novel data collection setup was adopted to record the vertical component of GRFs, and the footbridge vibration response during each trial. Frequency-domain analysis of both single-step and continuous GRFs was then performed. The results show that the footbridge vibration affects GRFs, and changes GRF magnitudes for harmonics in resonance with the footbridge vibration (up to around 30% reduction in the dynamic load factor of the third harmonic). This finding, and the measured GRFs, can be used for more accurate vibration serviceability assessments of existing and new footbridges.